The stellar orbit distribution in present-day galaxies inferred from the CALIFA survey. (March 2018) - Zhu, Ling; Ven, Glenn van de; Bosch, Remco van den; Rix, Hans-Walter; Lyubenova, Mariya; Falcón-Barroso, Jesús; Martig, Marie; Mao, Shude; Xu, Dandan; Jin, Yunpeng; Obreja, Aura; Grand, Robert; et al.
Abstract Galaxy formation entails the hierarchical assembly of mass, along with the condensation of baryons and the ensuing, self-regulating star formation1, 2 . The stars form a collisionless system whose orbit distribution retains dynamical memory that can constrain a galaxy's formation history3 . The orbits dominated by ordered rotation, with near-maximum circularityλ z  ≈ 1, are called kinematically cold, and the orbits dominated by random motion, with low circularityλ z  ≈ 0, are kinematically hot. The fraction of stars on 'cold' orbits, compared with the fraction on 'hot' orbits, speaks directly to the quiescence or violence of the galaxies' formation histories4, 5 . Here we present such orbit distributions, derived from stellar kinematic maps through orbit-based modelling for a well-defined, large sample of 300 nearby galaxies. The sample, drawn from the CALIFA survey6, includes the main morphological galaxy types and spans a total stellar mass range from 108.7 to 1011.9 solar masses. Our analysis derives the orbit-circularity distribution as a function of galaxy mass and its volume-averaged total distribution. We find that across most of the considered mass range and across morphological types, there are more stars on 'warm' orbits defined as 0.25 ≤ λ z  ≤ 0.8 than on either 'cold' or 'hot' orbits. This orbit-based 'Hubble diagram' provides a benchmark for galaxy formation simulations in a cosmological context. The distribution of circularity of stellar orbits within 300 galaxies of the present-day Universe, with masses between 108.7 and 1011.9 M ⊙, is directly observed by the CALIFA survey and provides a benchmark for galaxy simulations.